The Influence of Brand Ambassadors on Tokopedia Instagram Followers' Buying Interest - Nuraeni, Intan; Muslikhah, Febri Palupi; Lestari, Hana (JURNAL SAHID DA'WATII, 2022)
This study discusses the influence of brand ambassadors on buying interest in the followers of the Tokopedia Instagram account. The purpose of this study was to determine how much the relationship, influence and contribution of brand ambassadors to buying interest in the followers of the Tokopedia Instagram account. This type of research is a quantitative study with a correlational method. The correlational method used in this study is correlation and simple regression. This study shows a very strong positive relationship of 0.861 and has a significant positive effect of 0.000, while the contribution of brand ambassadors to purchase interest is 74.1%.